Factors Influencing Therapy and Dietary Adherence among Hemodialysis Patients: A Literature Review of Evidence from 2016–2026 - Hardi Yanis; Yenny Puspitasari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
Patients with Chronic Kidney Disease (CKD) undergoing hemodialysis require strict adherence to therapy schedules and dietary restrictions to prevent serious complications and improve quality of life. This study aims to identify and analyze various factors that influence therapy and diet adherence in patients undergoing hemodialysis. The study design was a literature review. Data sources were obtained from PubMed, ScienceDirect, and Google Scholar, Portal Garuda, SINTA, Google Scholar, and NDT with a publication period of 2017-2026. Of the total of 23 articles identified through a systematic search strategy, 16 articles met the PICOS (Population, Intervention, Comparison, Outcome, Study Design) inclusion criteria and were included in the analysis. The results of the analysis indicate that adherence is a multifactorial phenomenon. The findings revealed that family support and self-efficacy are more consistent determinants than factual knowledge. In addition, there is a shift in intervention trends from traditional educational methods to the use of m-Health technology and digital monitoring, which have been proven effective in improving control of patients' biochemical parameters. Conclusion: The novelty of this review lies in the integration of health behavior theories (Health Belief Model, Social Cognitive Theory, and Theory of Planned Behavior) which provides a holistic framework for adherence management. The main contribution of this study is to offer an adherence management model that combines psychosocial support, participatory education, and digital monitoring as an integrated intervention solution to improve patient clinical outcomes